Overcoming Self-Efficacy Challenges in Teachers and Prospective Teachers: Key Factors and Solutions - Menno, Ayu Windy Malisa; Simanjuntak, Yanni Irma Waty; Linda, Desma (Indonesian Journal of Educational Research and Review, 2024)
Self-efficacy relates to teachers' belief in their ability to carry out successful instruction and influences teachers to carry out their roles in learning. This literature review aims to explore the factors that influence teachers' and prospective teachers' self-efficacy, explore the challenges faced, and present solutions that may assist in enhancing self-efficacy. The method used is a literature review which includes planning, conducting, and reporting stages. 31 articles were used in this literature review obtained by searching and collecting in Scopus, Google Scholar, and ERIC databases, and through screening and selection based on inclusion criteria. Based on the results of the literature review, the factors that influence and pose challenges to the self-efficacy of teachers and prospective teachers are factors of practice and mastery of competencies, factors of differences in environment, culture, and student needs, factors of school organizational conditions and learning environments, and factors of pressure experienced by teachers and prospective teachers. The solutions to the self-efficacy challenges found include the implementation of education, training, and development programs, a good and collaborative school organization and environment, induction and mentoring programs, and attention to teacher welfare, counseling, and stress management. Collaboration between the government, educational institutions, schools, and communities is needed to develop the self-efficacy of teachers and prospective teachers and enhance the quality of education through supportive policies, a comprehensive curriculum, and a conducive learning environment.